Effects of ethanol preservation and formalin fixation on amino acid stable isotope analysis (δ13C and δ15N) and its ecological applications. (23rd January 2020) - Chua, Kenny W. J.; Liew, Jia Huan; Shin, Kyung‐Hoon; Yeo, Darren C. J.
Abstract: Compound‐specific isotope analysis of amino acids (CSIA‐AA) is a promising nascent technique that alleviates many shortcomings of conventional bulk‐tissue stable isotope analysis ("bulk SIA") in ecological studies involving the tracing/reconstruction of carbon and nitrogen pathways. While CSIA‐AA has been increasingly applied to preserved tissue samples (e.g., material in natural history collections), the effects of sample preservation on amino acid δ 13 C and δ 15 N profiles are poorly understood. It is therefore unclear if mathematical correction factors are necessary for interpreting isotopic profiles of preserved samples. In this study, we investigated effects of ethanol preservation and formalin fixation on amino acid δ 13 C and δ 15 N profiles. We also assess how these effects translate to two ecological applications of CSIA‐AA: quantification of organic carbon sources, and estimation of trophic positions. Results from an 8‐week controlled experiment on freshwater fish tissue show negligible preservation effects on most amino acid δ 15 N profiles, and results are similar for δ 13 C profiles of essential amino acids. Findings from mixing models using essential amino acid δ 13 C profiles similarly show that preserved samples can yield robust estimates of carbon source contributions. We also empirically demonstrate, for the first time, the use of amino acid δ 13 C profiles to enhance δ 15 N‐based estimates of trophic position in food webs with multiple producers, and show that these estimates are not compromised by preservation effects. Overall, our findings support the view that amino acid δ 13 C and δ 15 N profiles from ethanol‐ and formalin‐treated CSIA‐AA samples can be directly used for addressing ecological questions.